The Slovenian Armed Forces 15 years after the Republic of Slovenia joined NATO - Osterman, Andrej (Sodobni vojaški izzivi, 2019)
The Republic of Slovenia has been a NATO member for 15 years. Its NATO membership has significantly contributed to the quality development of the Slovenian Armed Forces (SAF), which has made a contribution to international security by taking part in international operations and missions. Before and after joining NATO, the SAF has adapted and transformed in view of the newly created settings and security challenges in a way to respond to them effectively. It has participated in and organized multinational military exercises, and has been operating within NATO representations, commands and units. NATO's deterrence posture strengthens the Alliance and requires an effective response to new sources of threat. The security environment is changing rapidly with hybrid and cyber threats becoming increasingly dangerous. NATO's long-term adaptation process requires members to respond to all potential sources of threat with a 360-degree approach. The Republic of Slovenia is also actively involved in the Smart Defence project, the Connected Forces Initiative and the Framework Nations Concept. The years-long decline in the defence budget has been reversed, which can, in the upcoming years, have a positive impact on the development of military capabilities for national needs and for the needs of the Alliance. For the Republic of Slovenia, NATO membership is still the most effective and rational solution to ensure its national security; however, the nation should lend solidarity by taking its share of the burden.
Keywords: adaptation; deterrence posture; mednarodno vojaško sodelovanje; military capabilities; Nato; Slovenian Armed Forces; Slovenija; vojska